Trade and economic growth : a Latin American perspective on rhetoric and reality - Moreno Brid, Juan Carlos (UN ECLAC Mexico, D.F.MX, 2009)
Analyses the different approaches to trade and growth in Latin America from the end of WWII to the present day. Examines specifically the underlying rhetoric of the alternative approaches and the extent to which the rhetoric matched understanding of Latin American reality.